LINGUISTIC FEATURES OF APPLICATION ELEMENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The study of applied elements in linguistics delves into the specific linguistic features and functions of words and structures that modify or refine the meaning of sentences. These elements, such as adjectives, adverbs, determiners, and various types of modifiers, enhance the flexibility and expressiveness of language. By exploring the unique roles these elements play in communication, this article examines how they function syntactically, semantically, and pragmatically, and how they are essential for both structural integrity and the conveyance of complex meanings in language.